Experiences of Science Teachers during the Pandemic-Based Distance Learning Process and Their Recommendations about the Post-Pandemic Process - Serpil Deli; Ozlem Koray; Emine Kahraman (Journal of Education in Science, Environment and Health)
The purpose of this study was to reveal the experiences of science teachers during the pandemic and their recommendations about the post-pandemic process. In the study, the “first period” referred to the period when the pandemic first appeared (the period between March-June 2020) and the “second period” referred to the post-summer holiday period (the period between August-November 2020). The study employed the phenomenology design, one of the qualitative research methods. For the study, one-on-one interviews were conducted with 16 science teachers working in the city of Sırnak. Interview data were analyzed using descriptive analysis and supported by direct quotations. Interview data were analyzed using descriptive analysis and supported by direct quotations. The study findings revealed that science teachers experienced problems in learning-teaching processes, assessment-evaluation, technical and structural situations due to the sudden transition to distance learning in the first period of the pandemic. In the second period of the pandemic, with the solving of technical and structural problems, teachers carried out a more systematic and planned teaching process compared to the first period. During this process, they enriched the learning environment with interactive experiments and materials, using different teaching methods and techniques. However, they stated that although they made changes in assessment and evaluation, they could not evaluate students sufficiently. In this context, teachers anticipated that students will have difficulty adapting to school after the pandemic, and they were of the opinion that the deficiencies of the pandemic process can be eliminated with make-up lessons.